OPTIMIZING THE ROLE OF COLLABORATION IN MAINTAINING MSME SUSTAINABILITY - Alhidayatullah Alhidayatullah (Jurnal Apresiasi Ekonomi, 2025)
Product and service innovation collaboration, marketing collaboration, and supply chain collaboration are strategies that can be done to improve the performance and sustainability of MSMEs in the current industrial revolution 4.0 era. The purpose of this study is to analyze and explain the optimization of the role of collaboration in maintaining the sustainability of MSMEs. The study's data, which consists of MSMEs in Sukabumi City, has a population of 31,926. Web.raosoft.com sample size was used, with an error rate of 5%, to ensure that a sample of 380 respondents was obtained. This study employed a quantitative, descriptive methodology. Respondents to a Google form including questions are given questionnaires as part of the data gathering process for this project. In this study, the analysis method employed was multiple linear regression analysis. The study's results explained that product and service innovation collaboration, marketing collaboration, and supply chain collaboration had a positive and significant effect on maintaining the sustainability of MSMEs and its influence was 64.4% while 35.6% was influenced by other variables that were not studied.